Persepsi Calon Guru Sains di Perguruan Tinggi Kabupaten Garut Terhadap Energi Nuklir dan PLTN dalam Mendukung Target Net Zero Emission - Salma Hanifah Riyahanna; Arip Nurahman; Nina Widiawati (STKIP Harapan Bima, 2025)
The transition toward Net Zero Emission (NZE) requires Indonesia to consider nuclear energy as a clean energy source. However, public perception, particularly among pre-service science teachers, remains varied. This study aims to identify the perception of pre-service science teachers in Garut Regency toward nuclear energy and nuclear power plants (NPP), to assess Indonesia's readiness to build an NPP by 2030, to determine the extent to which the curriculum supports knowledge related to NPP, and to identify the information media that support their understanding. A descriptive quantitative approach was used with a sample of 226 respondents, pre-service science teacher students from IPI and UNIGA. The results show that the majority of respondents still hold a negative perception of nuclear energy (34.51%), and 66.80% consider Indonesia not yet ready to build an NPP by 2030. The curriculum was considered inadequate by 70.35% of respondents, so 88.50% proposed adding a specific course. Field visits were rated as the most effective learning strategy by most respondents (62.37%), while social media remains the main information source used by 82.74% of respondents in seeking information about nuclear energy and NPP. The study affirms the need to strengthen the curriculum and educational strategies to improve knowledge related to nuclear energy and NPP.